Ganciclovir‐resistant cytomegalovirus infection in solid organ transplant recipients: a single‐center retrospective cohort study. Issue 3 (9th June 2016) - Young, P.G.; Rubin, J.; Angarone, M.; Flaherty, J.; Penugonda, S.; Stosor, V.; Ison, M.G.
Abstract: Background: Ganciclovir‐resistant cytomegalovirus (GCV‐R CMV) is an emerging challenge among solid organ transplant (SOT) recipients. The literature suggests that about 1% of abdominal transplant recipients develop GCV‐R CMV infection. The epidemiology and outcome of GCV‐R CMV in SOT recipients who have received alemtuzumab induction is not well described. Methods: After Institutional Review Board approval, a single‐center, retrospective review of 2148 abdominal SOT recipients between January 2006 and July 2011 at our institution ( n = 2148) was conducted to identify patients with proven or empirically treated GCV‐R CMV. Descriptive statistics on collected demographics, clinical course, and therapeutic outcomes were performed. Results: Of 116 SOT recipient treated for CMV, 14 patients (12.1% of cases; 0.65% of all SOT patients) had proven or suspected GCV‐R CMV. Eight (50%) developed GCV‐R CMV while receiving valganciclovir (valGCV) prophylaxis. The remainder developed late‐onset disease, after having completed an average 212 days (range 83–353) of prophylaxis. Resistance was clinically suspected an average of 103 days (range 10–455) after CMV infection was initially identified; 10 patients had confirmed genotypic resistance. Foscarnet therapy was associated with resolution of CMV in 13. Conclusion: Suboptimal dosing of valGCV is associated with development of GCV‐R CMV. Our observed rate of GCV‐R CMV in alemtuzumab‐induced patients is similar to rates seen to historical data for other induction agents.